Pelatihan Penggunaan Laboratorium Virtual Berbasis Aplikasi Phet Simulation di Kabupaten Kampar - Yeni Pertiwi; Rino Ferdian (Abdimas Universal, 2022)
Kampar Regency is located in the Riau Province. This district consists of 21 sub-districts where there are 140 SMA/SMK/MA/equivalent schools. The problem faced in several public and private schools in this region is the lack of laboratory facilities in carrying out science experiments in the field of physics. In addition, the time to conduct experiments in the physics laboratory is also very less due to the dense activities of teachers and students in achieving other competencies. The low skill of teachers in using virtual laboratory technology is also a major factor in not carrying out experiments in the field of physics, so that it has an impact on the low level of understanding of students. The solution offered in overcoming the problem is the use of a virtual laboratory in the implementation of experiments in the field of physics. The first step in overcoming the above problems is to provide socialization of the benefits of the Phet Simulation application. Furthermore, training on the use of physics teachers for SMA/SMK/MA in Kampar Regency was carried out. The training on the use of phet simulation applications given to 32 teacher participants has succeeded in increasing the knowledge and skills of participants by 12.7%. To achieve an increase in knowledge and skills of at least 80%, continuous mentoring must be carried out again for participants.